Maternal and Fetal Risks Associated with Teenage and Adult Pregnancy - Mehreen Mehdi (Journal of Rawalpindi Medical College, 2010)
Background: To compare the fetal and maternal complications between teenage and adult mothers. Methods: This comparative study included 200 teenage pregnant patients (15 – 19 years) and 200 adult pregnant patients(20-28 years). The fetal and maternal complications in both age group were compared. Results: Anaemia was more frequent in teenagers (30% vs 18%). Preterm delivery occurred in 28% of cases as compared to 12% in adult group. Spontaneous Vertex Delivery (SVD) was the mode of delivery in 73% of teenage group as compared to 65% of cases in adult group. Caesarean section was done in 10% of patients in teenage group as compared to 20% cases in adults while the rate of instrumental delivery was 8% vs 10%. Pregnancy Induced Hypertension occurred in 12% of teenagers group as compared to 5% in adult group . Eclampsia occurred in 8 patients of teenage group as compared to 3 patients of adult group. Diabetes was seen in 2% versus 12% in teenage and adult group, respectively. Low Apgar was noted in 12% of babies born to teenage age mothers as compared to 5% in adult group. Low birth weight babies were born more in teenage group as compared to adult group ( 20% vs 10%) Neonatal death occurred in 20 babies of teenage group as compared to 8 babies in adult group. Conclusion:Teenage mothers generally encounter more problems during pregnancy and child birth than older women. There is an increased risk of complications such as premature labour, anaemia and small for gestational age babies